Stem cell transplantation for the treatment of liver diseases: A systematic review and meta-analysis - Zishuai Liu; Junnan Li; Ping Li; Mei Bai; Yanjun Guo; Mingzi Han; Feifei Zhang; Robin Ahmed; Shizhu Jin (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The therapeutic efficacy of stem cell transplantation in liver diseases has not yet been determined. The objective of this study was to conduct a meta-analysis to evaluate changes in liver function and clinical outcome following stem cell transplantation in patients with liver disease. Materials and Methods: A literature review of NCBI, Cochrane Library, and MEDLINE was performed. Eligible studies reported liver function indices and prothrombin time (PT) before and after transplantation. The weighted mean difference (WMD) was defined by the distinction before and after stem cell transplantation. Either a fixed-effects model or random-effects model was used to analyze the data. Results: A total of 17 publications involving 21 original studies were included. We found that the levels of serum albumin significantly increased at 4, 8, 12, 24, and 48 weeks after stem cell transplantation compared with that at baseline. Serum alanine aminotransferase levels notably decreased at 1, 3, 4, 12, 24, and 48 weeks after stem cell transplantation. Aspartate aminotransferase levels significantly decreased at 4, 8, 12, and 48 weeks after transplantation. Total bilirubin levels significantly decreased at 4, 12, 24, and 48 weeks after transplantation. PT decreased at 4, 12, 24, and 48 weeks after transplantation. The MELD score significantly decreased at 24 weeks after transplantation. Stem cell infusion through the hepatic artery had better biochemical outcomes than an injection through the portal vein. Conclusion: Our meta-analysis verified that there are clinical and biochemical improvements in patients who suffered from liver diseases after stem cell transplantation, suggesting that stem cell transplantation may be a viable clinical solution for treating such patients.